Effectiveness of Audiovisual-based Pedagogy in Social Studies Instruction - Pangilinan, Joel R. (Journal of Education and Society, 2020)
A pretest-posttest based study was conducted to examine the effectiveness of an audio-visual method in teaching Social Studies among the Grade 9 students of Dolores National High School, Dolores, Eastern Samar. The use of the audio-visual method as an experimental treatment was compared against the traditional method of teaching for one month using lessons under Ang Daigdig sa Klasikal at Transisyunal na Panahon (The world in classical and transitional period). The data collected among 30-respondents per group were analyzed using mean, mean difference, standard deviation, and t-test for independent and dependent samples at 0.05 level of significance. Findings revealed that the use of the audio-visual method in teaching social sciences minimized extreme performances among the respondents and is statistically more effective than the traditional approach. Hence, the researcher recommends audio-visual instruction, especially among struggling learners and least learned topics.